Cell-Free DNA in Emergency Medical Care - A. D. Filev; V. M. Pisarev (Неотложная медицинская помощь, 2020)
ABSTRACT. Defining molecules with high prognostic value for predicting the course and outcomes of life-threatening sepsis, severe injuries, vascular accidents remains an urgent problem in emergency medicine. One of the promising candidate biomarkers of emergency states and critical illness is the content of extracellular DNA (exDNA) in blood plasma. The purpose of this review is to identify the prospects for the introduction of cfDNA in clinical medicine and the severities arose along this way. The levels and altered dynamics of the concentration of circulating DNA fragments, including the organ-specific fraction of exDNA seem informative today for assessing the degree of damage to the organ of interest, the probability of a complicated course and the prognosis of outcomes of emergency/critical illness in Intensive Care Unit (ICU) patients. Sources of exDNA circulating in the bloodstream may include the nuclei of dying cells from organs and tissues, damaged mitochondria, the pool of which should be remodeled with mitophagy, as well as microorganisms. Similarly to pathogen-associated molecules (PAMP) represented by fragments of bacterial and viral DNA, native DNA molecules associated with damage (DAMP) bind to toll-like receptors (TLR9) and intracellular DNA sensors (cGAS-STING, NLRP3), initiating the inflammatory processes in tissues and hemostatic disorders. These processes represent natural adaptive responses protecting against microbes, as well as disadaptation responses potentiating cell damage in organs. The increasing expression of genes encoding proinflammatory signaling pathways associated with NF-kB transcription factor and interferon-regulating factors (IRF), in turn, contribute to production of cytokines and other factors enhancing the stress-responses that alter the functional activity of cells in various organs. The available literature data suggest that the quantitative determining plasma exDNA, which serves as PAMP and DAMP to significantly contribute to pathogenesis of emergency states and critical illness, might aid in predicting the outcome and justifying the in-time personalization of treatment of emergency and post-emergency patients.